All-colloidal parity–time-symmetric microfiber lasers balanced between the gain of colloidal quantum wells and the loss of colloidal metal nanoparticles. Issue 37 (13th September 2022) - Foroutan-Barenji, Sina; Shabani, Farzan; Isik, Ahmet Tarik; Dikmen, Zeynep; Demir, Hilmi Volkan
Abstract : Spectral purification is demonstrated by harnessing notions from parity-time (PT) symmetry in an all-colloidal system of a whispering-gallery-mode (WGM) supported microfiber cavity independent from selected pumping. Abstract : Lasers based on semiconductor colloidal quantum wells (CQWs) have attracted wide attention, thanks to their facile solution-processability, low threshold and wide range spectral tunability. Colloidal microlasers based on whispering-gallery-mode (WGM) resonators have already been widely demonstrated. However, due to their microscale size typically supporting multiple modes, they suffer from multimode competition and higher threshold. The ability to control the multiplicity of modes oscillating within colloidal laser resonators and achieving single-mode lasers is of fundamental importance in many photonic applications. Here we show that as a unique, simple and versatile architecture of all-colloidal lasers intrinsically enabled by balanced gain/loss segments, the lasing threshold reduction and spectral purification can be readily achieved in a system of a WGM-supported microfiber cavity by harnessing the notions of parity–time symmetry (PT). In particular, we demonstrate a proof-of-concept PT-symmetric microfiber laser employing CQWs as the colloidal gain medium along with a carefully tuned nanocomposite of Ag nanoparticles (Ag NPs) incorporated into a PMMA matrix altogether and conveniently coated around a coreless microfiber as a rigorously tailored colloidal loss medium to balance the gain. The realization of gain/loss segments in our PT-symmetric all-colloidal arrangement is independent of selected pumping, reducing the complexity of the system and making compact device applications feasible, where control over the pumping is not possible. We observed a reduction in the number of modes, resulting in a reduced threshold and enhanced output power of the PT-symmetric laser. The PT-symmetric CQW-WGM microcavity architecture offers new opportunities towards simple implementation of high-performance optical resonators for colloidal lasers.